Accounting for Government in the Global South: do global solutions match local problems? - Stewart Lawrence; Andy Wynne (Australasian Accounting, Business and Finance Journal, 2009)
This paper examines the impact of globalised accounting and economic reforms on the public sectors of less developed countries. Our interest is in the international institutions that have been instrumental in introducing common, global remedies which appear to be based on theoretical understandings as opposed to experience of the effects of their interventions. A growing concern is being expressed about such interventions, but there is a sparcity of reports from the field. We argue that a re-think is required of type of the public sector financial management reforms which the international financial institutions and the national aid agencies have been promoting across the Global South for the last decade or so.